Modelling and analysis of transformers considering ultra‐wide band frequency‐dependent parameters for high altitude electromagnetic pulse - Han Wu; Nan Zhang; Jinhua Du; Junna Li; Shuai Dong; Zitao Lv (High Voltage)
Abstract Transformers are widely distributed and extremely important energy conversion equipment in the power system. However, the high altitude electromagnetic pulse (HEMP) can induce a steep pulse voltage with a peak value of up to thousands of kilovolts on the overhead line, and the frequency is up to 100 MHz, which is easy to damage the transformer and seriously threaten the safe and stable operation of the power system. Therefore, to protect the safety of the power system, analysing the transformer wave process under the action of HEMP is necessary. Accordingly, there is a need for an ultra‐wide band model of the transformer. In this paper, the skin effect of winding is analysed, the dielectric response of oil‐paper is fitted with the double relaxation Cole–Cole model, and the frequency dependent models of distribution parameters are established. Fractional order terms are introduced into the traditional multi‐conductor transmission line (MTL) integer order model to describe the characteristics of these distribution parameters so that the frequency application range of the MTL model is extended to 100 MHz. The proposed MTL model is solved by the finite‐difference time‐domain algorithm and verified by the finite element method and experiment. The error is less than 5%, which verifies its accuracy and effectiveness.